2000
DOI: 10.1093/oxfordjournals.jpart.a024260
|View full text |Cite
|
Sign up to set email alerts
|

The Government Performance and Results Act and the Tradition of Federal Management Reform: Square Pegs in Round Holes?

Abstract: Issue Section: Articles You do not currently have access to this article. Download all figures The argument of this article is that GPRA-like a number of earlier federal management reform efforts-does not fit easily into the institutional structures, functions, and p olitical realities of the American system. Desp ite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 7 publications
1
78
0
5
Order By: Relevance
“…Further, by holding public agencies accountable for performance, policymakers are able to get more "bang for the buck" by spending less money on programs that do not work and more on those that do. While performance budgeting has become ubiquitous at all levels of government in America over the last fifteen years (Kettl 2000;Melkers and Willoughby 1998;Moynihan 2006a), empirical research has generally found only limited evidence that performance information has a meaningful impact on budget decisions, particularly at the state and federal levels of government Lewis 2006b, 2006a;Joyce 1999;Long and Franklin 2004;Moynihan 2006b;Radin 2000). Why have policymakers been so apt to adopt performance mechanisms if they do not use the information that these systems generate ?…”
Section: Accountability and The Performance Movementmentioning
confidence: 99%
“…Further, by holding public agencies accountable for performance, policymakers are able to get more "bang for the buck" by spending less money on programs that do not work and more on those that do. While performance budgeting has become ubiquitous at all levels of government in America over the last fifteen years (Kettl 2000;Melkers and Willoughby 1998;Moynihan 2006a), empirical research has generally found only limited evidence that performance information has a meaningful impact on budget decisions, particularly at the state and federal levels of government Lewis 2006b, 2006a;Joyce 1999;Long and Franklin 2004;Moynihan 2006b;Radin 2000). Why have policymakers been so apt to adopt performance mechanisms if they do not use the information that these systems generate ?…”
Section: Accountability and The Performance Movementmentioning
confidence: 99%
“…Most studies have condemned the way organizations implement performance management system (PMS), emphasizing that the processes, measures and data are flawed (Grizzle, 2002;Radin, 2000;Schick, 2001;Wiseman, 2004). This argument at higher level of organizations requires renew effort both theoretical and practical issues which may have causes decrease in performance improvement.…”
Section: Performance Management System (Pms)mentioning
confidence: 99%
“…Public sector discourse from the late 20th century has been dominated by the demand for higher performance from government organizations (Radin 2000). One result of this narrative has been a greater emphasis on performance management as well as a broad results-based orientation for public organizations (Kettl 2000).…”
Section: Performance Management and The Question Of Employee Performancementioning
confidence: 99%
“…Performance management at the organizational level is moreover a cyclical process whereby managers utilize performance information to continually adjust objectives and make decisions for achieving organizational goals (Andersen 2008;Moynihan 2008) with the express goal of improving program outcomes and other relevant goals (Heinrich 2002;Radin 2000). Performance management is firmly rooted in the tradition of rational approaches to an organization's performance (Boyne 2010, quoted in Walker et al 2011), and is a relatively broad topic that incorporates elements of internal and external communication, financial management, decentralization, and other concepts.…”
Section: Organization-level Performance Managementmentioning
confidence: 99%